Rancang Bangun Aplikasi Virtual Tour Wisata Bukit Kambo Highland Berbasis Web - Kurniadi, Wisnu; Jusriati, Jusriati; H, Fahrul; Mukassaf, Mukassaf (LPPM UNIKA Santo Thomas, 2023)
This research aims to design and develop a web-based virtual tour application that will provide users with an interactive experience in exploring the Bukit Kambo Highland tourist destination. This application is the focus of research because of its great potential in promoting and simplifying the experience of tourists who are interested in the charm of Bukit Kambo Highland. In the development process, the Multimedia Development Live Cycle (MDLC) approach was used which includes six important stages: Concept, Design, Material Collection, Manufacturing, Testing, and Distribution. The design stage is an important moment in the development of this application, where the Unified Modeling Language (UML) is used to clearly describe the structure and flow of interaction between the user and the system. This application is equipped with various features, such as interactive map navigation, playback of explanatory videos about interesting locations, and a user-friendly interface. Application testing was carried out using the Black Box Testing method, which produced very positive results in terms of functionality, performance, compatibility and interface. With satisfactory test results, this application is expected to be an effective promotional tool for Bukit Kambo Highland, providing users with an immersive virtual tour experience, and overcoming physical limitations in exploring tourist destinations. It is also hoped that this application will make a positive contribution to tourism promotion and the development of web-based technology, enriching the tourist experience and supporting the growth of the tourism industry.